2006
DOI: 10.1007/s00280-006-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Glucose uptake inhibitor sensitizes cancer cells to daunorubicin and overcomes drug resistance in hypoxia

Abstract: Cancer cells heavily rely on glucose transporters for glucose uptake to facilitate a high-rate glycolysis under hypoxia for their survival and drug resistance. Combination of glucose transporter inhibitors and chemotherapeutic drugs may provide a preferential novel therapeutic strategy to overcome drug resistance in hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(132 citation statements)
references
References 31 publications
3
129
0
Order By: Relevance
“…2DG is currently in clinical trials for use as a chemotherapeutic agent. Several studies have furthermore shown a synergistic effect of 2DG in combination with other cancer therapeutics, including HDAC inhibitors (43,44). Therapeutic synergy has been shown between a novel HDAC inhibitor LAQ824 (that can pass the blood-brain barrier) and 2DG in treatment of glioblastoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…2DG is currently in clinical trials for use as a chemotherapeutic agent. Several studies have furthermore shown a synergistic effect of 2DG in combination with other cancer therapeutics, including HDAC inhibitors (43,44). Therapeutic synergy has been shown between a novel HDAC inhibitor LAQ824 (that can pass the blood-brain barrier) and 2DG in treatment of glioblastoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased glucose consumption serves to supply carbon to various anabolic pathways necessary for biomass duplication preceding mitosis 33 and induces resistance to classic chemotherapeutic agents. 10,34,35 Compelled by evidence that glucose transport may represent the principal ratedetermining step of glycolysis in tumor cells, 13,14 we have interrogated the glucose transporter family as a source of novel therapeutic targets. Our data clearly demonstrate myeloma dependence on GLUT4 activity, a phenomenon associated with the basal cell surface localization of the transporter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the combination of WZB117 which is a Glut1 inhibitor and cisplatin or paclitaxel displayed synergistic anticancer effects (12). Another GLUT1 inhibitor phloretin significantly enhanced daunorubicin's anticancer effects under hypoxia (13). Moreover, 3-BrPA which is a glycolysis inhibitor partially reversed the resistant phenotype and re-sensitized cells to oxaliplatin and 5-fluorouracil (14).…”
Section: Introductionmentioning
confidence: 99%